Left incarcerated or strangulated obturator hernia: a case report - Mohanan, Athira (International Surgery Journal, 2022)
Obturator hernia is an extremely rare type of hernia with relatively high mortality and morbidity. Its early diagnosis is challenging since the signs and symptoms are non-specific. Obturator hernia is a rare but significant cause of intestinal obstruction especially in emaciated elderly women. Here a case of 93-year frail lady with incarcerated left sided obturator hernia with small bowel as content is presented, for which she underwent resection and ileoileal anastomosis and simple closure of the hernia defect.